Delayed small-intestinal transit in tropical malabsorption. Issue 6132 (22nd July 1978) - Cook, G C
Abstract : The time of breath hydrogen appearance (T) after oral lactulose was determined in 98 patients in London who had been to the tropics. Fifty-six controls from three different ethnic groups had no evidence of gastrointestinal disease; 23 had tropical malabsorption, which was severe in 10; and 19 had chronic diarrhoea without malabsorption. Mean T was significantly delayed in patients with tropical malabsorption compared with controls, indicating that their mouth-caecum transit rate was abnormally slow. In six patients with tropical malabsorption who were reinvestigated after treatment a fall in the value for T seemed to parallel clinical improvement. Three patients with diarrhoea due to chronic colonic disease had delayed T. Patients with tropical malabsorption have bacterial colonisation of the small intestine, which is important in the pathogenesis of the disease. Bacterial overgrowth, which sometimes occurs after infective diarrhoea in the tropics and gives rise to tropical sprue, is a result of stasis.